A General and Facile Approach for the Electrochemical Reduction of Carbon Dioxide Inspired by Deep Eutectic Solvents. Issue 8 (1st April 2019) - Vasilyev, Dmitry V.; Rudnev, Alexander V.; Broekmann, Peter; Dyson, Paul J.
Abstract: Deep eutectic solvents (DESs) were applied to the electrochemical CO2 reduction reaction (CO2 RR). Choline‐based DESs represent a non‐toxic and inexpensive alternative to room‐temperature ionic liquids (RTILs) as additives to the system or as electrolyte. Following the study on choline‐based DESs this approach was generalized and simple and organic‐soluble systems were devised based on the combination of organic chloride salts with ethylene glycol (EG), allowing the chlorides to be readily used as cocatalysts in the CO2 RR. This approach negates the need for anion exchange and, because the chloride salt is usually the least expensive one, substantially reduces the cost of the electrolyte and opens the way for high‐throughput experimentation. Abstract : Still waters run deep : Cheap and simple deep eutectic solvents provide a versatile route to highly efficient and inexpensive electrolytes/cocatalysts for electrochemical reduction of CO2 .